الآثار الاقتصادية المتوقعة للشراكة السورية _ الأوربية - زنبوعة, محمود; أبا زيد, ثناء; اسمندر, إيهاب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هذا البحث يتحدث عن الآثار الاقتصادية للشراكة السورية _ الأوربية على سورية، إذ إنها إحدى المواضيع الهامة جداً بالنسبة لسورية هذه الأيام بسبب العولمة والإصلاحات الاقتصادية. وتناولنا هنا الآثار على ثلاثة قطاعات مهمة, وهي : أولاً : الاستثمار الأوربي في سورية . ثانياً : الصناعة السورية . ثالثاً : القطاع الزراعي . وفي نهاية البحث وضعنا خاتمة على شكل مقترحات وتوصيات . This study deals with the anticipated economic effects of the European-Syrian partnership on Syria, for the partnership is a very important issue for Syrian nowadays, because of globalization and economic reforms. In particular, the study addresses the effects in three areas: First: European investment in Syria. Second: Syrian industry. Third: The Agricultural sector. Finally, the study offers suggestions and recommendations.